Use of polyhouse for improving the quality of rubber plants - Mercykutty V C; Mydin K K (Rubber Board Bulletin, 2012)
Polybag nursery experiments were conducted at the Central Experiment Station of the Rubber Research Institute of India, at Chethackal with the objectives to compare sprouting and growth of green and brown budded stumps planted in polybags kept in polyhouse and outdoor. Budded stumps generated from both green and brown budding techniques recorded early emergence of buds and better and uniform growth of scion in polyhouse conditions. Plants raised in polyhouse were better in terms of height of scion, diameter of stem, number of whorls, number of lateral roots and total biomass content. The study showed that growing plants inside polyhouse improved the quality of plants. The use of polyhouse gave protection to the grafts against diseases and reduction in mortality due to adverse weather conditions and ensured production of healthy plants. The improved technique resolved the main problems associated with the establishment of green budgrafts due to small stock with little starch reserve where severe die back of sprouted shoots were encountered. Hence, total recovery and usage of polybag plants are significantly more in polyhouse than in outdoor conditions. In aaddition to saving manpower cost, this modern technology is an ecofriendly approach as the use of fungicide is minimized inside the polyhouse condition.
Keywords: Polyhouse rubber plants